Declining Trends of Heart Rate Variability According to Aging in Healthy Asian Adults - Choi, Jungmi; Cha, Wonseok; Park, Min-Goo (Frontiers in Aging Neuroscience, 2020)
Heart rate variability (HRV) indices correlate with aging and are related to the autonomic nervous system. However, the trend of HRV with age has not been explored for the Asian population. Therefore, we proposed a linear regression model of HRV indices that decreased with aging in healthy Asian adults. HRV parameters (HF, LF, VLF, TP, HRV-index, SDNN and pNN50) were measured in a total of 300 healthy participants (150 men and 150 women) aged 19–69 years stratified into five age groups: 19–29, 30–39, 40–49, 50–59, and 60–69 years comprising 60 people each in Seoul, Korea. A simple regression analysis was performed to reveal the linear declining trend of HRV indices with age. Independent t-tests were conducted to investigate the gender differences in HRV values depending on each age group. The values of all HRV indices showed a decreasing trend with age in healthy Korean adults, as observed in the Western population (P<0.001 for all indices); HF (Y=-0.039x+6.833, R2=0.287), LF (Y=-0.047x+7.197, R2=0.414), VLF (Y=-0.025x+6.861, R2=0.177), TP (Y=-0.034x+8.082, R2=0.352), HRV-index (Y=-0.125x+15.628, R2=0.298), SDNN (Y=-0.502x+53.907, R2=0.343), and pNN50 (Y=-0.650x+53.852, R2=0.345) all decreased with age. There was no significant gender difference in any HRV parameter. A linear regression model of various HRV indices has been presented considering the age of healthy Asians, which may be useful to prevent diseases related to the autonomic nervous system by estimating or tracking autonomic functional degeneration in the Asian population.